PENERAPAN SISTEM INFORMASI AKUNTANSI PEMBAYARAN PADA PEMBERIAN IZIN TINGGAL KUNJUNGAN WNA DI KANTOR IMIGRASI KELAS I KHUSUS TPI NGURAH RAI - Gede Crisna Wijaya; Ni Luh Putu Mas Ashita Trisnayanti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the Payment Accounting Information System for Foreign Visit Stay Permits and to find out whether the applied SIA can encourage a better service system in granting Foreign Visit Stay Permits at the TPI Ngurah Rai Special Class I Immigration Office. The data collection technique was carried out by analyzing and presenting the data obtained through interviews and study documentation related to the payment system for stay permits for foreign visits conducted at the TPI Ngurah Rai Immigration Office. The result found is that the payment of a stay permit for a foreigner's visit uses the Non-Tax State Revenue (PNBP) system which is automatically integrated with the information system at the Ministry of Finance. Also the system for granting stay permits for foreign visits has been carried out using the Immigration application managed by the Directorate General of Immigration. Both of these systems make it easier for users to carry out payment activities for applicants and provide residence permits for immigration officials because they are automatically systemized and interconnected with the department or division concerned.